Development of C-Pd electrode as a working electrode in the detection of dissolved oxygen by cyclic voltammetry - Setiawan, Mohamad Bayu; Mulyono, Tri; Siswoyo (Indonesian Chimica Letters, 2023)
Dissolved oxygen in water is vital in supporting life, so it becomes one of the parameters of water quality and makes dissolved oxygen measurement very important. This study attempts to develop an electrode based on carbon-palladium alloy material (C-Pd) to be used as a voltammetric detector of dissolved oxygen in water. The formation of the alloy is carried out by electrodeposition using the cyclic voltammetry technique. The effect of HCl concentration in the palladium electrodeposition process is studied to obtain the optimum HCl concentration. The resulting C-Pd electrode is then tested for its performance in measuring dissolved oxygen. It is carried out by cyclic voltammetry in NaOH electrolyte solution, Ag/AgCl reference electrode, and Pt counter electrode. Before standard solutions and samples are measured, the NaOH concentration is optimized first to obtain the best oxygen reduction conditions on the Pd surface. The results of oxygen measurements with the C-Pd electrode are compared with those from a commercial DO meter. The results showed that palladium electrodeposition on the carbon surface was optimum in 0.5 M HCl solution, and the optimum dissolved oxygen reduction process used 0.1 M NaOH electrolyte solution. The results of the C-Pd electrode performance test showed a decrease in sensitivity in the form of a calibration curve slope value of -703.77 nA/ppm on the first day, -558.36 nA/ppm on the second day, and -417.81 nA/ppm on the third day. A comparison of measurement results between the C-Pd electrode and a commercial DO sensor showed a significant difference. Despite the less-than-optimal results, this study shows the potential for palladium to be used as an electrode in an electrochemical oxygen sensor as an alternative electrode material besides precious metals.